Investors’ Attention and American Depository Receipts Pricing: Evidence from Indian Stocks - Babu, A Sarath (Asian Journal of Empirical Research, 2019)
This paper is an attempt to examine the impact of investors’ attention on returns and the traded volume of American Depository Receipts prices for selected ten Indian Stocks. The Google search volume index has been used as a proxy for investors’ attention in this paper. However, factors such as size and book to market ratio were used to indicate as control variables. The results reveal that investors’ attention variable significantly affects ADRs traded volume, but has no impact on the ADR prices.